"SPEECH": A literature based framework for the study of past epidemics. Issue 3 (March 2022) - Kousoulis, Antonis A.; Grant, Imogen
Abstract: Introduction: This paper details the development of a public health research framework for the holistic examination of past epidemics. The Covid-19 pandemic has further highlighted the influence of a breadth of determinants of infectious disease morbidity and mortality. These are multidisciplinary and act in conjunction with each other. Hence, a broader interdisciplinary framework is required to conduct a comprehensive in-depth study of past epidemics and pandemics which focuses, not only on the epidemiology, but also on the broader political, social, economic and cultural factors which impact upon the public's risk perception and response to infectious disease outbreaks. Methods: A literature review was performed based on a systematic approach framework. Publications of interest were identified through a search of PubMed/Medline, the Cochrane Library and Google Scholar, the latter especially for additional grey literature, and reference lists were hand searched for further articles to include. Key determinants were extracted and classified based initially on the European Core Health Community Indicators (ECHIs), and further refined through narrative summary. Results: A total of 45 studies were identified, 13 of which fulfilled the inclusion criteria of comprehensive secondary research. A total of 26 determinants were extracted from the 13 publications, including microbiological, socioeconomic, political, meteorological and genetic determinants. Of the 26 identified factors, those prioritised were the 16 most relevant to the aim of applying a public health, rather than a narrow medical, lens to studying epidemics through considering a broader ecosystem of influences. The 16 determinants were summarised and categorised into the SPEECH (Society and Politics, Economy, Epidemiology, Culture, Healthcare and Public Health) framework. Conclusion: The interdisciplinary SPEECH framework set out in this paper provides the structure for the systematic and holistic in-depth investigation of past epidemics, incorporating the multitude of contextual factors which impact upon infectious disease outbreaks and the public's response to them at a national level.